2023
DOI: 10.1039/d2tb02639b
|View full text |Cite
|
Sign up to set email alerts
|

Polymerization-induced emission (PIE) of multifunctional polyamides synthesized by Ugi polymerization and targeted imaging of lysosomes

Abstract: In this paper, a series of polyamide derivatives (PAMs) containing morpholine groups were prepared by Ugi polymerization from dialdehyde, diacid, N-(2-aminoethyl)-morpholine and isonitrile compounds as the novel multi-responsive fluorescent sensors....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…110 112 Deng et al prepared a series of polyamide derivatives (PAMs) containing pendent morpholine groups, which endow polymerization-induced emission, and applied them to target imaging trackers and as real-time monitors of changes of Fe 3+ concentration in lysosomes. 113 Tomalia, Klajnert-Maculewicz et al showed that a functionalized PAMAM dendrimer forms a polyplex with double stranded DNA and is nontoxic for HeLa and HMEC-1 cells up to a concentration of 10 mg/mL. The unique intrinsic luminescence properties of the dendrimer revealed that it accumulates in endosomal compartments.…”
Section: Room-temperature Phosphorescence (Rtp)mentioning
confidence: 99%
See 1 more Smart Citation
“…110 112 Deng et al prepared a series of polyamide derivatives (PAMs) containing pendent morpholine groups, which endow polymerization-induced emission, and applied them to target imaging trackers and as real-time monitors of changes of Fe 3+ concentration in lysosomes. 113 Tomalia, Klajnert-Maculewicz et al showed that a functionalized PAMAM dendrimer forms a polyplex with double stranded DNA and is nontoxic for HeLa and HMEC-1 cells up to a concentration of 10 mg/mL. The unique intrinsic luminescence properties of the dendrimer revealed that it accumulates in endosomal compartments.…”
Section: Room-temperature Phosphorescence (Rtp)mentioning
confidence: 99%
“…Ding et al investigated peptidomimetic polyurea derivatives with AIE characteristics for conformation-assisted deformation, discoloration, and intracellular drug delivery with effective cancer theranosis in vitro and in vivo . Deng et al prepared a series of polyamide derivatives (PAMs) containing pendent morpholine groups, which endow polymerization-induced emission, and applied them to target imaging trackers and as real-time monitors of changes of Fe 3+ concentration in lysosomes . Tomalia, Klajnert-Maculewicz et al showed that a functionalized PAMAM dendrimer forms a polyplex with double stranded DNA and is nontoxic for HeLa and HMEC-1 cells up to a concentration of 10 mg/mL.…”
Section: Macromolecules With Nonconventional Luminescencementioning
confidence: 99%